Hepatitis C: improving the quality of screening in a community hospital by implementing an electronic medical record intervention. Issue 1 (20th May 2015) - Shahnazarian, Vahe; Karu, Eric; Mehta, Parag
Abstract: Both the Centers for Disease Control and Prevention (CDC) and the U.S. Preventive Services Task Force (USPSTF) have recommended that adults born between the years of 1945-1965 should receive one-time testing for Hepatitis C Virus (HCV). In fact, Governor Andrew Cuomo of the State of New York had signed a bill on October 23, 2013 which mandated NY hospitals and healthcare providers to offer HCV testing to all "Baby Boomers." For our project, we wanted to increase our community hospital's compliance with this law and improve the quality of patient care in doing so. An electronic medical record intervention was implemented in conjunction with our information technology services department. This intervention would flag eligible patients and would run them through a predetermined algorithm to see if they needed HCV testing. Multiple plan, do, study, act (PDSA) cycles were run during the length of the study and many changes were made in order to achieve maximum effect. We ended up increasing our HCV testing rate from 47.2% (pre-intervention) to 87.9% (final month of the study), which was statistically significant with a p-value of <0.0000001. We also ended up with a framework that is both generalizable to other projects and is also self-sustaining, so that it can continue to run itself once all the project members have finished working there as house staff.